AKUNTABILITAS LEMBAGA PENGELOLA WAKAF - Achmad Arief Budiman (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
Although wakaf has much importance for social living and practiced since a long time ago, but in fact wakaf has not maximally functioned. Still much numbers of people living under poor line level showed this fact. Some causes make wakaf is not effective. In one side, the cause is related to the human resources, especially in the side of the organizer (nāẓir). Other cause is the weakness of the accountability of wakaf institution. Applying doctrinal and non-doctrinal approach, this research showed that in PKPU the organizer implemented the principle of transparency and accountability in managing waqaf in the institution. The principle of accountability is implemented in the form of audit, both internally and externally by public accountant. Applying the principle of accountability had been increasing the publict trust to the wakaf institution.